(untitled) (Agricultural Engineering, 2016)
The load values corresponding to the compressive strength of high-bush blueberry and redcurrant fruits during the compression test between two rigid plates were measured. The changes of coefficient of elasticity and coefficient of viscosity values during the creep and the relaxation tests were studied in the selected interval of time, also direction of load application in relation to the longitudinal axis of fruit was considered. The creep and relaxation tests were carried out with the load of 40% of determined compressive strength of berries. To describe behavior of testing the material rheological standard, Maxwell and Kelvin models as well as experimental models were used. Comparatively small changes of parameter values of assumed empirical models were reported in the course of tests. It may be recognized as characteristic for the investigated material.